Life Insurance - A Comparative Perspective Between Romania and Russia - Ion PIRGARU; Mair AMZA; Raluca Ana VASILESCU; Carol Cristina GOMBOS; Cristian Alexandru VASILESCU (Communications of International Proceedings, 2021)
This research paper will address the different dimensions and challenges of the Romanian life insurance industry in contrast to those in the Russian Federation and the performance of the sector in the mentioned countries. Both Romania and Russia represent relatively mature markets in terms of life insurance providers. The purpose of life insurance is to provide financial security to policyholders and their families. Traditionally, this guarantee has been provided through a lump sum payable according to the death or survival of the insured life. The insured amount would be fixed and guaranteed. The insured would pay one or more premiums during the contract for the right to the insured amount.
Keywords: demand; health insurance; life insurance; Romania; Russia